PENERAPAN WEB PROXY DAN MANAGEMENT BANDWIDTH MENGGUNAKAN MIKROTIK ROUTERBOARD PADA KANTOR POS PALEMBANG 30000 - Tamsir Ariyadi; A Taufan Maulana (Teknik Informatika, 2021)
The Palembang 30000 POS office which is supported by information technology has a computer network that is directly connected to the ISP (Internet Service Provider) which has a bandwidth allocation of 20 Mbps. The problem at the Palembang 30000 POS Office is that there is no web proxy and Bandwidth Management application, so employees can access various sites that interfere with employee performance and employees who use the internet for free result in uneven bandwidth usage. The purpose of this study is to implement a web proxy and bandwidth management, so that the bandwidth is evenly distributed, therefore it is necessary to divide the bandwidth using a proxy routerboard, the method used for bandwidth distribution is using the simple queue method. By implementing a web proxy, it can control internet usage and block website sites that have the potential to interfere with employee performance, by making bandwidth management able to limit bandwidth usage and share bandwidth equally on each client, so internet access is now running more stable.